Method for producing a composition, crosslinked rubber article
By mixing a mixture of fluorinated copolymer (A) and fluorinated copolymer (B) at high temperature, the problems of easy cracking and insufficient plasma resistance of cross-linked rubber articles under high temperature and high compression are solved, and cross-linked rubber articles with excellent plasma resistance are achieved.
Patent Information
- Application Number
- CN202480081968.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-27
- Filing Date
- 2024-12-23
- Publication Date
- 2026-07-24
AI Technical Summary
Existing cross-linked rubber products are prone to cracking under high temperature and high compression conditions, and have insufficient resistance to plasma.
The mixture of fluorinated copolymer (A) and fluorinated copolymer (B) is compounded above the glass transition temperature of fluorinated copolymer (B). Fluorinated copolymer (A) has tetrafluoroethylene and perfluorinated (alkyl vinyl ether) based units, and fluorinated copolymer (B) has specific functional groups, tetrafluoroethylene and perfluorinated (alkyl vinyl ether) units, and their respective contents and compounding conditions are controlled to achieve uniform dispersion.
It effectively suppresses cracking under high temperature and high compression and improves plasma resistance, forming cross-linked rubber products with excellent plasma resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing a composition and cross-linked rubber articles. Background Technology
[0002] From the perspective of its excellent heat resistance, chemical resistance, oil resistance and weather resistance, cross-linked rubber articles made by cross-linking fluorinated copolymers are widely used as sealing materials (such as O-rings, gaskets, oil seals and washers) and cushioning materials in vehicles, ships, aircraft, general machinery and construction.
[0003] As a method for manufacturing a composition using such a cross-linked rubber article, Patent Document 1 discloses a method for manufacturing a composition comprising a specific fluorinated copolymer.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: International Publication No. 2021 / 210502 Summary of the Invention
[0007] The problem the invention aims to solve
[0008] In recent years, there has been a demand across various fields for improved performance of cross-linked rubber articles, specifically for cross-linked rubber articles that exhibit crack suppression under high temperature and high compression conditions and excellent plasma resistance.
[0009] In response to such requirements, the inventors evaluated a cross-linked rubber article formed using a composition manufactured by the method described in Patent Document 1, and found that it was prone to cracking during compression set tests under high temperature and high compression conditions, and that there was room for improvement in plasma resistance.
[0010] The objective of this invention is to provide a method for manufacturing a composition capable of forming a cross-linked rubber article that can suppress cracking under high temperature and high compression and has excellent plasma resistance, as well as the cross-linked rubber article.
[0011] Solution for solving the problem
[0012] The inventors conducted in-depth research and found that the above-mentioned problems can be solved by the following configuration. [1]
[0014] A method for manufacturing a composition includes a mixing step of mixing a mixture comprising a fluorinated copolymer (A) and a fluorinated copolymer (B) above the glass transition temperature of the fluorinated copolymer (B).
[0015] The aforementioned fluorinated copolymer (A) has tetrafluoroethylene-based units and perfluoro(alkyl vinyl ether)-based units.
[0016] The fluorinated copolymer (B) described above is a copolymer different from the fluorinated copolymer (A) described above, having units based on monomers having at least one functional group selected from the group consisting of a carboxyl group and a group represented by formula (X) described later, units based on tetrafluoroethylene, and units based on perfluorinated (alkyl vinyl ether). [2]
[0018] According to the method of manufacturing the composition described in [1], wherein the fluorinated copolymer (A) comprises units having nitrile groups. [3]
[0020] According to the method for manufacturing the composition described in [1] or [2], the above-mentioned mixing step is a step of mixing the above-mentioned mixture at a melting point above the above-mentioned fluorinated copolymer (B). [4]
[0022] The method for manufacturing the composition according to any one of [1] to [3], wherein, in the above mixture, the content of the above fluorinated copolymer (B) is 50 parts by mass or less relative to 100 parts by mass of the above fluorinated copolymer (A). [5]
[0024] The method for manufacturing the composition according to any one of [1] to [4], wherein the fluorinated copolymer (A) is a fully fluorinated copolymer. [6]
[0026] A crosslinked rubber article is formed by crosslinking the above-mentioned fluorinated copolymer (A) in a composition manufactured by the manufacturing method of any one of [1] to [5] using a crosslinking agent. [7]
[0028] The cross-linked rubber article described in [6] is a sealing material for semiconductor devices.
[0029] The effects of the invention
[0030] According to the present invention, a method for manufacturing a composition capable of forming a cross-linked rubber article that can suppress cracking under high temperature and high compression and has excellent plasma resistance, and a cross-linked rubber article, are provided. Detailed Implementation
[0031] The meanings of the terms used in this invention are as follows.
[0032] The range of values represented by "~" refers to the range of values recorded before and after "~" as the lower and upper limits.
[0033] "Unit" refers to the atomic group directly formed by the polymerization of monomers, originating from one molecule of the aforementioned monomer, and the atomic group obtained by chemically transforming a portion of the aforementioned atomic group. "Monomer-based unit" is also referred to as "unit" below.
[0034] "Rubber" refers to rubber exhibiting the properties defined by JIS K 6200:2008, as opposed to "resin".
[0035] [Method for manufacturing the composition]
[0036] The method for manufacturing the composition of the present invention (hereinafter also referred to as "the manufacturing method") includes a mixing step of mixing a mixture comprising a fluorinated copolymer (A) and a fluorinated copolymer (B) above the glass transition temperature of the fluorinated copolymer (B), wherein the fluorinated copolymer (A) has tetrafluoroethylene-based units and perfluoro(alkyl vinyl ether)-based units, and the fluorinated copolymer (B) is a copolymer different from the fluorinated copolymer (A) having units based on a monomer having at least one functional group selected from the group consisting of a carboxyl group and a group represented by formula (X) described later, tetrafluoroethylene-based units, and perfluoro(alkyl vinyl ether)-based units.
[0037] Crosslinked rubber articles made using this manufacturing method exhibit excellent resistance to cracking under high temperature and high compression, as well as superior plasma resistance. The exact reasons for this are not yet clear, but it is speculated that they are due to the following factors.
[0038] It is speculated that by mixing the above mixture above the glass transition temperature of the fluorinated copolymer (B), the fluorinated copolymer (B) can be uniformly dispersed in the fluorinated copolymer (A), resulting in the suppression of cracking of the obtained crosslinked rubber article under high temperature and high compression, and excellent plasma resistance.
[0039] Hereinafter, the effect of being able to suppress cracks under high temperature and high compression and having excellent plasma resistance will be referred to as "the effect of the present invention".
[0040] <Mixture>
[0041] The mixture used in this manufacturing method comprises a fluorinated copolymer (A) and a fluorinated copolymer (B).
[0042] The mixture preferably does not contain the crosslinking agent described later.
[0043] The mixture preferably consists only of fluorinated copolymer (A) and fluorinated copolymer (B). Specifically, the total content of fluorinated copolymer (A) and fluorinated copolymer (B) relative to the total mass of the mixture is preferably 90 to 100% by mass, more preferably 95 to 100% by mass, and even more preferably 99 to 100% by mass.
[0044] (Fluoropolymer (A))
[0045] The fluorinated copolymer (A) has units based on tetrafluoroethylene (hereinafter also referred to as "TFE") and units based on perfluoro(alkyl vinyl ether) (hereinafter also referred to as "PAVE").
[0046] Fluorinated copolymer (A) cannot fully recover from elongation, but exhibits a property that is strengthened by cross-linking, that is, it exhibits the properties of rubber.
[0047] The content of TFE units relative to all units of the fluorinated copolymer (A) is preferably 60.0 to 80.0 mol%, more preferably 63.0 to 75.0 mol%, and even more preferably 66.0 to 72.0 mol%.
[0048] The PAVE unit is based on perfluorinated (alkyl vinyl ether) units.
[0049] From the perspective of excellent polymerization reactivity and rubber properties, PAVE prefers the monomer shown in formula (1).
[0050] CF2 = CF - OR f2 (1)
[0051] In equation (1), R f2 It refers to perfluoroalkyl groups with 1 to 10 carbon atoms.
[0052] From the perspective of superior polymerization reactivity, R f2 The number of carbon atoms is preferably 1 to 8, more preferably 1 to 6, even more preferably 1 to 5, and particularly preferably 1 to 3.
[0053] Perfluoroalkyl groups can be linear or branched.
[0054] Specific examples of PAVE include perfluoro(methyl vinyl ether) (hereinafter also referred to as "PMVE"), perfluoro(ethyl vinyl ether) (hereinafter also referred to as "PEVE") and perfluoro(propyl vinyl ether) (hereinafter also referred to as "PPVE"), with PMVE or PPVE being preferred.
[0055] From the perspective of superior elasticity of cross-linked rubber articles, the content of PAVE units relative to all units of the fluorinated copolymer (A) is preferably 20.0 to 40.0 mol%, more preferably 24.0 to 36.0 mol%, and even more preferably 27.0 to 33.0 mol%. When PMVE or PPVE is used as PAVE, the preferred content is also the same.
[0056] Fluorinated copolymer (A) preferably has monomers with nitrile groups in addition to units based on TFE monomers and units based on PAVE monomers (hereinafter also referred to as "R"). CN The unit of ”).
[0057] From the viewpoint that the present invention offers superior performance, R CN Preferably, it also has fluorine atoms, and more preferably, it is a monomer represented by formula (2).
[0058] CR 11 R 12 =CR 13 -R 14 -CN (2)
[0059] In equation (2), R 11 R 12 and R 13 Each can independently represent a hydrogen atom, a fluorine atom, or a methyl group. R 14 It refers to a perfluorocarbon group with 1 to 10 carbon atoms in a divalent state, or a group having an ether-like oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds.
[0060] From R CN Based on its excellent polymerization reactivity, R 11 R 12 and R 13 Preferably, it contains fluorine or hydrogen atoms, more preferably R. 11 R 12 and R 13 All atoms are fluorine or hydrogen atoms. From the perspective of superior release properties and heat resistance of cross-linked rubber articles, R is further optimized. 11 R 12 and R 13 It consists entirely of fluorine atoms.
[0061] R 14 It can be any of the following: linear, branched, and cyclic, preferably linear or branched. R 14 The number of carbon atoms is preferably 2 to 8, more preferably 3 to 7, even more preferably 4 to 7, and particularly preferably 4 to 6.
[0062] R 14 The crosslinked rubber article is preferably provided with an ether-containing oxygen atom, from the perspective of superior rubber properties.
[0063] R 14 The number of ether oxygen atoms in the sample is preferably 1 to 3, more preferably 1 or 2.
[0064] Specific examples of the monomers shown in formula (2) include CF2=CFOCF2CF(CF3)OCF2CF2CN (hereinafter also referred to as "8CNVE"), CF2=CFO(CF2)5CN (hereinafter also referred to as "MV5CN"), CF2=CFOCF2CF2CF2OCF(CF3)CN and CF2=CFO(CF2)3CN. From the viewpoint that the crosslinked rubber articles have better release properties and heat resistance, 8CNVE or MV5CN is preferred.
[0065] From the perspective of achieving better results with the present invention, R CN The content of the unit relative to all units of the fluorinated copolymer (A) is preferably 0.05 to 5 mol%, more preferably 0.1 to 3 mol%, and even more preferably 0.2 to 1.5 mol%.
[0066] Fluorinated copolymer (A) may have units based on monomers other than those described above (hereinafter also referred to as "other monomers").
[0067] Specific examples of other monomers include vinylidene fluoride (hereinafter also referred to as "VdF"), hexafluoropropylene (hereinafter also referred to as "HFP"), trifluorochloroethylene, monomers having two or more polymerizable unsaturated bonds (hereinafter also referred to as "BO"), monomers shown in formula (6), ethylene, propylene and monomers having halogen atoms (hereinafter also referred to as "other monomers having halogen atoms").
[0068] Other examples of monomers containing halogen atoms include bromotrifluoroethylene and iodotrifluoroethylene.
[0069] The BO unit is a unit based on monomers having two or more polymerizable unsaturated bonds.
[0070] Specific examples of polymerizable unsaturated bonds include carbon-carbon double bonds (C=C) and carbon-carbon triple bonds (C≡C).
[0071] From the perspective of superior polymerization reactivity, the number of polymerizable unsaturated bonds in BO is preferably 2 to 6, more preferably 2 or 3, and even more preferably 2.
[0072] From the perspective that cross-linked rubber articles have less compression set at high temperatures, BO also contains fluorine atoms.
[0073] From the perspective that compression set becomes smaller under high temperature and high compression, the monomer shown in formula (3) is preferred by BO.
[0074] (CR 31 R 32 =CR 33 ) a3 R34 (3)
[0075] In equation (3), R 31 R 32 and R 33 Each atom independently represents a hydrogen atom, a fluorine atom, a methyl group, or a trifluoromethyl group. a3 represents an integer from 2 to 6. R 34 This refers to a perfluorocarbon group with 1 to 10 carbon atoms in the α3 valence, or a group having an ether-like oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds. Multiple R 31 Multiple R 32 and multiple R 33 Each can choose to be the same as or different from the others, with the preference being that they are the same.
[0076] a3 is preferably 2 or 3, more preferably 2.
[0077] From the perspective that BO has superior polymerization reactivity, R 31 R 32 and R 33 Preferably, it contains fluorine or hydrogen atoms, more preferably R. 31 R 32 and R 33 Composed entirely of fluorine or hydrogen atoms, R is further preferred from the perspective of heat resistance and chemical resistance of cross-linked rubber articles. 31 R 32 and R 33 It consists entirely of fluorine atoms.
[0078] R 34 It can be any of the following: linear, branched, and cyclic, preferably linear or branched, and more preferably linear. R 34 The number of carbon atoms is preferably 2 to 10, more preferably 3 to 8, even more preferably 3 to 6, and particularly preferably 3 to 5.
[0079] R 34 The crosslinked rubber article is preferably provided with an ether-containing oxygen atom, from the perspective of superior rubber properties.
[0080] R 34 The number of ether-containing oxygen atoms is preferably 1 to 6, more preferably 1 to 3, and even more preferably 1 or 2. R 34 The ether oxygen atom in R is preferably present in R 34 The end of.
[0081] Among the monomers shown in formula (3), specific examples of preferred monomers include the monomers shown in formula (4) and formula (5).
[0082] (CF2=CF)2R 41 (4)
[0083] In equation (4), R 41 It refers to a perfluorocarbon group with 2 to 10 carbon atoms in a divalent state, or a group having an ether-like oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds.
[0084] Specific examples of the monomers shown in equation (4) include CF2=CFO(CF2)2OCF=CF2, CF2=CFO(CF2)3OCF=CF2, CF2=CFO(CF2)4OCF=CF2, CF2=CFO(CF2)6OCF=CF2, CF2=CFO(CF2)8OCF=CF2, CF2=CFO(CF2)2OCF(CF3)CF2OCF=CF2, and CF2=CFO(CF2)2O(CF(CF3)CF2O)2CF=C F2, CF2=CFOCF2O(CF2CF2O)2CF=CF2, CF2=CFO(CF2O)3O(CF(CF3)CF2O)2CF=CF2, CF2=CFOCF2CF(CF3)O(CF2)2OCF (CF3)CF2OCF=CF2 and CF2=CFOCF2CF2O(CF2O)2CF2CF2OCF=CF2, preferably CF2=CFO(CF2)3OCF=CF2 or CF2=CFO(CF2)4OCF=CF2.
[0085] (CH2=CH)2R 51 (5)
[0086] In equation (5), R 51 It refers to a perfluorocarbon group with 2 to 10 carbon atoms in a divalent state, or a group having an ether-like oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds.
[0087] Specific examples of the monomers shown in formula (5) include CH2=CH(CF2)2CH=CH2, CH2=CH(CF2)4CH=CH2 and CH2=CH(CF2)6CH=CH2, with CH2=CH(CF2)6CH=CH2 being preferred.
[0088] When BO is copolymerized, the polymerizable double bonds at the ends of BO react during polymerization to obtain a branched fluorinated copolymer (A).
[0089] CF2 = CF - OR f6 (6)
[0090] In equation (6), R f6 R represents a perfluoroalkyl group with 1 to 8 carbon atoms and containing 1 to 5 ether-containing oxygen atoms. f6 The number of carbon atoms is preferably 1 to 6, more preferably 1 to 5.
[0091] Specific examples of the monomers shown in formula (6) include perfluorinated (3,6-dioxa-1-heptene), perfluorinated (3,6-dioxa-1-octene), and perfluorinated (5-methyl-3,6-dioxa-1-nonene).
[0092] When the fluorinated copolymer (A) contains other monomer units, from the perspective of excellent rubber properties of the crosslinked rubber article, the content of other monomer units is preferably 0.01 to 20 mol% relative to all units of the fluorinated copolymer (A), more preferably 0.5 to 10 mol%, and even more preferably 1 to 5 mol%.
[0093] From the perspective of further improving the effects of the present invention, the fluorinated copolymer (A) is preferably a fully fluorinated fluorinated copolymer.
[0094] "Fully fluorinated fluorinated copolymers" refer to fluorinated copolymers that substantially do not contain hydrogen atoms bonded to carbon atoms, but instead have fluorine atoms in place of the hydrogen atoms, and whose main chain is composed of carbon atoms. The side chains of fully fluorinated fluorinated copolymers may have multivalent atoms other than carbon atoms; oxygen atoms are preferred as such multivalent atoms.
[0095] "Substantially contains no hydrogen atoms" means that the hydrogen atom content in the fully fluorinated fluorinated copolymer is 0.5% by mass or less, preferably 0.1% by mass or less, more preferably 0.07% by mass or less, and even more preferably 0.05% by mass or less. When the hydrogen atom content is within the above range, good heat resistance or chemical resistance is easily obtained.
[0096] The fluorinated copolymer (A) may contain iodine atoms. In this case, it is preferable that the iodine atoms are located at the ends of the polymer chains of the fluorinated copolymer (A).
[0097] Examples of iodine atoms include iodine atoms derived from iodine compounds that function as chain transfer agents (described later), iodine atoms in units of monomers containing iodine atoms such as iodotrifluoroethylene described above, and preferably iodine atoms derived from iodine compounds that function as chain transfer agents.
[0098] When the fluorinated copolymer (A) contains iodine atoms, the content of iodine atoms relative to the total mass of the fluorinated copolymer (A) is preferably 0.01 to 5.0% by mass, more preferably 0.05 to 2.0% by mass, and even more preferably 0.05 to 1.0% by mass. When the content of iodine atoms is within the above range, the crosslinking reactivity of the fluorinated copolymer (A) is improved, and the mechanical properties of the crosslinked rubber article are excellent.
[0099] The glass transition temperature of the fluorinated copolymer (A) is preferably -20~20℃, more preferably -10~10℃, and even more preferably -5~5℃.
[0100] The glass transition temperature of the fluorinated copolymer (A) can be determined using a differential scanning calorimeter (DSC). Specifically, it is determined using the method described in the Examples section below.
[0101] The glass transition temperature of a fluorinated copolymer (A) can be adjusted by the type of unit constituting the fluorinated copolymer (A), the proportion of that unit, and the molecular weight. For example, the higher the proportion of TFE units, the higher the glass transition temperature of the fluorinated copolymer (A) tends to be.
[0102] The content of the fluorinated copolymer (A) relative to the total mass of the mixture is preferably 60 to 99% by mass, more preferably 70 to 99% by mass, and even more preferably 80 to 99% by mass.
[0103] As an example of a method for manufacturing fluorinated copolymer (A), a method of copolymerizing the above monomers in the presence of a free radical polymerization initiator can be cited.
[0104] Water-soluble polymerization initiators or redox polymerization initiators are preferred as free radical polymerization initiators.
[0105] Specific examples of water-soluble polymerization initiators include persulfate-based initiators such as ammonium persulfate, sodium persulfate, and potassium persulfate, and organic polymerization initiators such as disuccinate peroxide and azobisisobutylamidine dihydrochloride, with persulfate-based initiators being preferred, and ammonium persulfate being more preferred.
[0106] Examples of redox polymerization initiators include polymerization initiators composed of persulfates and reducing agents, with preferred initiators capable of polymerizing monomers within a polymerization temperature range of 0 to 85°C. Specific examples of persulfates constituting redox polymerization initiators include alkali metal salts of persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate, with ammonium persulfate being preferred. Specific examples of reducing agents combined with persulfates include thiosulfates, sulfites, bisulfites, metabisulfites, and hydroxymethanesulfinates, with hydroxymethanesulfinates being preferred, and sodium hydroxymethanesulfinate more preferred.
[0107] In the method for manufacturing the fluorinated copolymer (A), the monomer described above can be copolymerized with a free radical polymerization initiator in the presence of a chain transfer agent.
[0108] The chain transfer agent is preferably an iodine compound, more preferably an iodine compound represented by formula RI2. In the above formula, R represents an alkylene group or a perfluoroalkylene group having 3 or more carbon atoms (preferably 3 to 8 carbon atoms).
[0109] Specific examples of iodine compounds represented by formula RI2 include 1,3-diiodopropane, 1,4-diiodobutane, 1,6-diiodohexane, 1,8-diiodooctane, 1,3-diiodoperfluoropropane, 1,4-diiodoperfluorobutane, 1,6-diiodoperfluorohexane, and 1,8-diiodoperfluorooctane.
[0110] As an iodine compound, an iodine compound having a perfluoroalkylene group is preferred, and 1,4-diiodoperfluorobutane is more preferred.
[0111] When the above monomers are copolymerized in the presence of these iodine compounds, iodine atoms can be introduced into the fluorinated copolymer (A).
[0112] For details regarding the components other than those described above used in the manufacture of the fluorinated copolymer (A), please refer to the methods described in paragraphs 0019 to 0034 of International Publication No. 2010 / 082633.
[0113] (Fluoropolymer (B))
[0114] Fluorinated copolymer (B) is a copolymer different from fluorinated copolymer (A) having: a unit having at least one functional group (hereinafter also referred to as "specific functional group") selected from the group consisting of carboxyl group and group represented by formula (X), a TFE unit and a PAVE unit.
[0115] In other words, the fluorinated copolymer (B) has: units with specific functional groups, TFE units, and PAVE units.
[0116] The specific functional group can be any or both of the carboxyl group and the group shown in formula (X).
[0117] Formula (X) *-CO-O-CO-*
[0118] In equation (X), * represents the bonding position.
[0119] The unit having a specific functional group is preferably based on a monomer having a specific functional group (hereinafter also referred to as "R"). X The unit of ”).
[0120] R X It can have multiple specific functional groups. R X In the case of having multiple specific functional groups, the types of the multiple specific functional groups can be chosen to be the same or different from each other.
[0121] R X As a monomer, it therefore possesses polymerizable unsaturated bonds. Specific examples of polymerizable unsaturated bonds are described above.
[0122] R XPreferably, it is a compound having one specific functional group and one polymerizable unsaturated bond.
[0123] Examples of monomers containing a carboxyl group include itaconic anhydride (hereinafter also referred to as "IAH"), citraconic anhydride (hereinafter also referred to as "CAH"), 5-norbornene-2,3-dicarboxylic anhydride (also known as Nadic anhydride, hereinafter also referred to as "NAH"), and maleic anhydride, which are anhydrides of unsaturated dicarboxylic acids.
[0124] As a group containing the group shown in formula (X), it is preferred to be a group formed by removing one hydrogen atom from an acid anhydride.
[0125] Examples of monomers having the group shown in formula (X) include itaconic anhydride (hereinafter also called "IAH"), citraconic anhydride (hereinafter also called "CAH"), 5-norbornene-2,3-dicarboxylic anhydride (also called nadic anhydride, hereinafter also called "NAH"), maleic anhydride, and other anhydrides of unsaturated dicarboxylic acids.
[0126] From the perspective of reactivity with the nitrile groups that may be present in the fluorinated copolymer (A), R X The monomer preferably contains a group having the group shown in formula (X), and more preferably contains at least one selected from the group consisting of IAH, CAH and NAH, and even more preferably contains NAH, especially preferably NAH.
[0127] R X You can use one type alone, or you can use two or more types together.
[0128] The TFE and PAVE units of the fluorinated copolymer (B) are the same as those of the fluorinated copolymer (A).
[0129] Fluorinated copolymer (B) may have units based on monomers other than those described above (hereinafter also referred to as "other monomers"). Specific examples and preferred embodiments of other monomers are the same as those of other monomers in fluorinated copolymer (A).
[0130] Fluorinated copolymers (B) can further have specific functional groups as end groups of the main chain.
[0131] Specific functional groups that are terminal groups of the main chain can be introduced by free radical polymerization initiators and chain transfer agents used in the manufacture of fluorinated copolymers (B).
[0132] From the perspective of further improving the effects of the present invention, the content of the unit having a specific functional group is preferably 0.01 to 3 mol% relative to all units of the fluorinated copolymer (B), more preferably 0.03 to 2 mol%, and even more preferably 0.05 to 1 mol.
[0133] From the perspective of further improving the effects of the present invention, the content of TFE unit relative to all units of the fluorinated copolymer (B) is preferably 90 to 99.89 mol%, more preferably 95 to 99.47 mol%, and even more preferably 96 to 98.95 mol%.
[0134] From the perspective of further improving the effects of the present invention, the content of PAVE units relative to all units of the fluorinated copolymer (B) is preferably 0.1 to 9.99 mol%, more preferably 0.5 to 4.97 mol%, and even more preferably 1 to 3.95 mol%.
[0135] The glass transition temperature of the fluorinated copolymer (B) is preferably 40°C or higher, more preferably 50°C or higher, even more preferably 60°C or higher, and particularly preferably 70°C or higher. The upper limit is preferably 150°C or lower, more preferably 120°C or lower, even more preferably 100°C or lower, and particularly preferably 90°C or lower.
[0136] The glass transition temperature of the fluorinated copolymer (B) can be determined using a differential scanning calorimeter (DSC). Specifically, it is determined using the method described in the Examples section below.
[0137] The melting point of the fluorinated copolymer (B) is preferably 250°C or higher, more preferably 270°C or higher, even more preferably 290°C or higher, and particularly preferably 295°C or higher. The upper limit is preferably 330°C or lower, more preferably 325°C or lower, even more preferably 315°C or lower, even more preferably 312°C or lower, and particularly preferably 310°C or lower.
[0138] When the melting point of the fluorinated copolymer (B) is above the lower limit of the above range, the crosslinked rubber articles made from the mixture containing the fluorinated copolymer (B) exhibit excellent heat resistance. Furthermore, when the melting point is below the upper limit of the above range, the processability is excellent, and the surface smoothness of the crosslinked rubber articles made from the composition containing the fluorinated copolymer (B) is excellent.
[0139] The melting point of the fluorinated copolymer (B) can be determined using a differential scanning calorimeter (DSC). Specifically, it is determined using the method described in the Examples section below.
[0140] The glass transition temperature and melting point of fluorinated copolymers (B) can be adjusted by the type of units constituting the fluorinated copolymer (B), the proportion of those units, and their molecular weight. For example, the higher the proportion of TFE units, the higher the melting point of the fluorinated copolymer (B) tends to be.
[0141] The melt flow rate (MFR) of the fluorinated copolymer (B) is preferably 1 to 1000 g / 10 min, more preferably 10 to 35 g / 10 min. The MFR mentioned above is a value measured at a temperature at least 20°C higher than the melting point of the fluorinated copolymer (B) (typically 372°C).
[0142] When the MFR is above the lower limit of the above range, the fluorinated copolymer (B) has excellent processability, and the cross-linked rubber articles made from mixtures containing the fluorinated copolymer (B) have excellent surface smoothness.
[0143] When the MFR is below the upper limit of the above range, the fluorinated copolymer (B) has excellent mechanical strength, and the cross-linked rubber articles made from mixtures containing the fluorinated copolymer (B) have excellent mechanical strength.
[0144] MFR is a benchmark for the molecular weight of fluorinated copolymers (B). A higher MFR indicates a smaller molecular weight, and a lower MFR indicates a larger molecular weight. MFR can be adjusted by the molecular weight of the fluorinated copolymer (B) and its manufacturing conditions. For example, shortening the polymerization time during monomer polymerization tends to increase the MFR.
[0145] From the perspective of further improving the effects of the present invention, the content of fluorinated copolymer (B) relative to 100 parts by weight of fluorinated copolymer (A) is preferably 50 parts by weight or less, more preferably 30 parts by weight or less, and even more preferably 20 parts by weight or less.
[0146] The content of fluorinated copolymer (B) relative to 100 parts by mass of fluorinated copolymer (A) is preferably 2 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 7 parts by mass or more.
[0147] The content of the fluorinated copolymer (B) relative to the total mass of the mixture is preferably 1 to 40% by mass, more preferably 1 to 30% by mass, and even more preferably 1 to 20% by mass.
[0148] As an example of a method for manufacturing fluorinated copolymer (B), a method of copolymerizing the above monomers in the presence of a free radical polymerization initiator can be cited, the details of which are described in International Publication No. 2016 / 017801.
[0149] The fluorinated copolymer (B) is preferably in the form of particles. That is, the fluorinated copolymer (B) is preferably in the form of copolymer particles containing the fluorinated copolymer (B).
[0150] The copolymer particles may contain polymers other than fluorinated copolymers (A) and fluorinated copolymers (B) (hereinafter also referred to as "other polymers").
[0151] Other polymers include fluorinated polymers other than fluorinated copolymers (A) and fluorinated copolymers (B), such as tetrafluoroethylene-fluoroalkyl vinyl ether copolymers, tetrafluoroethylene-hexafluoropropylene copolymers and ethylene-tetrafluoroethylene copolymers, polytetrafluoroethylene, aromatic polyesters, polyamide-imides and thermoplastic polyimides.
[0152] The content of fluorinated copolymer (B) in the copolymer particles is preferably 80 to 100% by mass relative to the total mass of the polymer particles, more preferably 85 to 100% by mass, even more preferably 90 to 100% by mass, and particularly preferably 99.99 to 100% by mass.
[0153] From the perspective of further improving the effects of the present invention, the particle size D50 of the copolymer particles is preferably 0.02~50µm, more preferably 0.02~35µm, and even more preferably 0.02~10µm.
[0154] The particle size D50 of the copolymer particles is the cumulative 50% diameter based on the volume reference obtained by laser diffraction and scattering (D50). That is, it is the particle size at the point where the cumulative volume of the particle group becomes 50% by setting the total volume of the particle group to 100% through the particle size distribution determined by laser diffraction and scattering.
[0155] Copolymer particles can be manufactured, for example, by the method for manufacturing resin particles and resin powder described in International Publication No. 2016 / 017801.
[0156] <Process>
[0157] (Mixing process)
[0158] This manufacturing method includes a mixing step of mixing the above mixture at a temperature above the glass transition temperature of the fluorinated copolymer (B).
[0159] By implementing the above-described mixing process, the fluorinated copolymer (A) and the fluorinated copolymer can be easily and uniformly mixed, thus achieving the effects of the present invention.
[0160] As a method of mixing, well-known mixing methods can be cited, with the method of mixing using a mixing machine being preferred.
[0161] Specific examples of mixing machines include roller mixers, kneader mixers, Banbury mixers, and extruders. Extruders are preferred in terms of mixing properties, temperature control, and production stability.
[0162] Examples of extruders include those equipped with heating devices and barrels with vents, such as single-screw extruders, twin-screw extruders, or multi-screw extruders. Extruders can be used individually or in series, with multiple extruders of the same or different types connected together. When using twin-screw extruders, examples include non-meshing co-rotating, meshing co-rotating, non-meshing counter-rotating, and meshing counter-rotating types.
[0163] Specific examples of extruders include LABO PLASTOMILL (manufactured by Toyo Seiki Co., Ltd.) and Plastic-Corder Lab-Station (manufactured by Brabender Co., Ltd.).
[0164] The mixing temperature is above the glass transition temperature of the fluorinated copolymer (B), and preferably above the melting point of the fluorinated copolymer (B). The glass transition temperature and melting point of the fluorinated copolymer (B) are as described above. In addition, the mixing temperature is also preferably above the glass transition temperature of the fluorinated copolymer (A), and more preferably above the melting point of the fluorinated copolymer (A).
[0165] Specifically, the mixing temperature is preferably above 80°C, more preferably above 200°C, even more preferably above 240°C, and particularly preferably above 270°C. The upper limit is preferably below 350°C, more preferably below 340°C, even more preferably below 330°C, and particularly preferably below 320°C.
[0166] The mixing time is preferably 0.1 to 60 minutes, more preferably 1 to 30 minutes, and even more preferably 1.5 to 15 minutes.
[0167] The rotational speed of the rotating body (e.g., blades and rotating shaft) is preferably 1 to 500 rpm, more preferably 10 to 250 rpm, and even more preferably 50 to 150 rpm.
[0168] There are no particular limitations on the method of supplying the fluorinated copolymer (A) and the fluorinated copolymer (B) to the mixer. Specifically, the fluorinated copolymer (A) and the fluorinated copolymer (B) can be pre-mixed to obtain a mixture, and then the mixture can be supplied to the mixer. Alternatively, the fluorinated copolymer (A) and the fluorinated copolymer (B) can be supplied to the mixer separately. From the perspective of the superior effects of the present invention, the method of supplying the mixture to the mixer is preferred, and the pre-mixing process described later is more preferred.
[0169] The mixing process can be carried out once or twice or more.
[0170] (Premixing process)
[0171] This manufacturing method preferably includes a premixing process.
[0172] The premixing process is performed before the mixing process described above.
[0173] The effects of this invention can be easily achieved through a pre-mixing process.
[0174] The premixing process is a process of mixing fluorinated copolymer (A) and fluorinated copolymer (B) at a temperature lower than the glass transition temperature of fluorinated copolymer (B) to obtain a mixture (hereinafter also referred to as "premix").
[0175] The mixing methods can be exemplified by the mixing processes described above, with the mixing method using a mixing machine being preferred, and the mixing method using a roller mixer being even more preferred.
[0176] The mixing temperature is lower than the glass transition temperature of the fluorinated copolymer (B). The glass transition temperature of the fluorinated copolymer (B) is as described above. Furthermore, the mixing temperature is also preferably lower than the glass transition temperature of the fluorinated copolymer (A).
[0177] Specifically, the mixing temperature is preferably 20~60℃, more preferably 22~55℃.
[0178] The mixing time is preferably 1 to 30 minutes, more preferably 5 to 15 minutes.
[0179] The rotational speed of the rotating body (e.g., blades and rotating shaft) is preferably 100 to 2000 rpm, more preferably 500 to 1500 rpm.
[0180] The premixing process can be carried out once or twice or more.
[0181] The premix may contain other ingredients besides those described above without impairing the effects of the invention.
[0182] Other components include additives that do not undergo vulcanization reactions with fluorinated copolymers (A) and (B) due to temperature, such as imide-based additives with imide structures like polyimide, polyamide-imide, and polyether-imide; organic additives made from engineering plastics such as polyarylates, polysulfones, polyethersulfones, polyphenylene sulfides, polyether ether ketones, polyether ketones, polyoxybenzoic acid esters, and liquid crystal polymers; phosphorus-based additives such as trioctylphosphine; metal oxide additives such as alumina, silicon oxide, and yttrium oxide; metal carbides such as silicon carbide and aluminum carbide; metal nitride additives such as silicon nitride and aluminum nitride; and inorganic additives such as aluminum fluoride, fluorinated carbon, and carbon black.
[0183] [Fluorine-containing copolymer composition]
[0184] The fluorinated copolymer composition of the present invention comprises a composition obtained by the method for manufacturing the above composition and a crosslinking agent.
[0185] There are no particular limitations on the composition as long as it is obtained by the above-described method of manufacturing the composition.
[0186] Crosslinking agent
[0187] Fluorinated copolymer compositions contain crosslinking agents.
[0188] Specific examples of crosslinking agents include organic peroxides and compounds having two or more amino groups (hereinafter also referred to as "polyamine compounds"). From the perspective of obtaining crosslinked rubber articles with excellent crosslinking properties of fluorinated copolymers (A) and less compression set under high temperature and high compression, polyamine compounds are preferred.
[0189] The polyamine compound can be a compound in which hydrogen atoms of aliphatic hydrocarbons are replaced by amino groups, or a compound in which hydrogen atoms of aromatic hydrocarbons are replaced by amino groups. From the perspective of the superior effects of the present invention, a compound in which hydrogen atoms of aromatic hydrocarbons are replaced by amino groups is preferred.
[0190] The polyamine compound preferably contains fluorine atoms. As a result, the compatibility with the fluorinated copolymer (A) becomes good, and thus cross-linked rubber articles with lower compression set under high temperature and high compression can be obtained.
[0191] Specific examples of polyamine compounds include hexamethylenediamine, hexamethylenediamine carbamate, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (hereinafter also called "BOAP", alternative name, bisaminophenol AF), 2,2-bis(3,4-diaminophenyl)propane, 2,2-bis(3,4-diaminophenyl)hexafluoropropane, 2,2-bis(3-amino-4-(N-phenylamino)phenyl)hexafluoropropane, 4,4'-methylenediphenylamine, m-phenylenediamine, adipic acid dihydrazide, and compounds of formula (XII) in Japanese Patent No. 5833657. From the viewpoint of further improving the effects of the present invention, BOAP is preferred.
[0192] The content of the crosslinking agent relative to 100 parts by weight of the fluorinated copolymer (A) is preferably 0.3 to 10 parts by weight, more preferably 0.3 to 5 parts by weight, and even more preferably 0.5 to 3 parts by weight. When the content of the crosslinking agent is within the above range, the effects of the present invention are more superior.
[0193] <Other Ingredients>
[0194] Fluorinated copolymer compositions may contain other components besides those described above without impairing the effects of the present invention.
[0195] Specific examples of other components include acid absorbents (e.g., fatty acid esters, fatty acid metal salts, oxides of divalent metals (magnesium oxide, calcium oxide, zinc oxide, and lead oxide, etc.)), fillers and reinforcing materials (e.g., carbon black, barium sulfate, calcium metasilicate, calcium carbonate, titanium dioxide, silicon dioxide, fluorinated copolymers other than fluorinated copolymers (A) and fluorinated copolymers (B) (e.g., tetrafluoroethylene-fluoroalkyl vinyl ether copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, and ethylene-tetrafluoroethylene copolymers, etc.), polytetrafluoroethylene (PTFE), aromatic polyesters, polyamide-imides and thermoplastic polyimides, clay, talc), scorch inhibitors (e.g., compounds containing phenolic hydroxyl groups such as bisphenol A, quinones such as hydroquinone, α-methylstyrene dimers such as 2,4-di(3-isopropylphenyl)-4-methyl-1-pentene), crown ethers (e.g., 18-crown-6), and release agents (e.g., sodium stearate).
[0196] When the fluorinated copolymer composition contains other components, the total content of the other components is preferably 0.1 to 30 parts by weight relative to 100 parts by weight of the fluorinated copolymer (A), more preferably 1 to 15 parts by weight, and even more preferably 3 to 5 parts by weight.
[0197] As a method for manufacturing fluorinated copolymer compositions, one example is a method of mixing the above composition with a crosslinking agent (post-mixing step).
[0198] The mixing temperature in the subsequent mixing process is preferably lower than the glass transition temperature of the fluorinated copolymer (B), which is as described above. Furthermore, the mixing temperature is also preferably lower than the glass transition temperature of the fluorinated copolymer (A).
[0199] The mixing temperature is preferably 20~60℃, more preferably 22~55℃.
[0200] The mixing time is preferably 1 to 30 minutes, more preferably 5 to 15 minutes.
[0201] The rotational speed of the rotating body (e.g., blades and rotating shaft) is preferably 1 to 500 rpm, more preferably 5 to 50 rpm.
[0202] The following manufacturing method is preferred as a method for manufacturing the fluorinated copolymer composition.
[0203] A method for manufacturing a fluorinated copolymer composition includes a pre-mixing step of mixing a fluorinated copolymer (A) and a fluorinated copolymer (B) at a temperature lower than the glass transition temperature of the fluorinated copolymer (B) to obtain a mixture.
[0204] The mixing process involves kneading the obtained mixture above the glass transition temperature of the aforementioned fluorinated copolymer (B) to obtain the composition.
[0205] A post-mulling step of obtaining a fluoropolymer composition by mixing the resulting composition with a crosslinking agent
[0206] In the above mixture, the above fluoropolymer (A) has units based on tetrafluoroethylene and units based on perfluoro(alkyl vinyl ether).
[0207] In the above mixture, the above fluoropolymer (B) is a copolymer different from the above fluoropolymer (A), and has units based on a monomer having at least one functional group selected from the group consisting of a carboxyl group and a group represented by the following formula (X), units based on tetrafluoroethylene, and units based on perfluoro(alkyl vinyl ether).
[0208] Each component and each step in the above manufacturing method are as described above.
[0209] In addition, after obtaining the fluoropolymer composition in which the above components are mixed, the fluoropolymer composition can be molded.
[0210] As a specific example of the molding method of the fluoropolymer composition, compression molding, injection molding, extrusion molding, calendering molding, and a method of dissolving in a solvent, impregnating, and coating for molding can be cited.
[0211] [Crosslinked rubber article]
[0212] The crosslinked rubber article of the present invention is a rubber article obtained by crosslinking the fluoropolymer (A) in the above fluoropolymer composition.
[0213] As a crosslinking method of the fluoropolymer (A) in the present fluoropolymer composition, a method of crosslinking by heating the present fluoropolymer composition is preferred.
[0214] As a specific example of the crosslinking method by heating, hot press crosslinking, steam crosslinking, injection molding crosslinking, hot air crosslinking, molten salt crosslinking, flow crosslinking, and rotary crosslinking (corresponding to Japanese: ロート架橋) can be cited.
[0215] The heating conditions are preferably 1 second to 24 hours at 100 to 400 °C.
[0216] The crosslinked rubber obtained by heating the present fluoropolymer composition (primary crosslinking) can be further heated for secondary crosslinking. By performing secondary crosslinking, the mechanical properties, compression set, and other properties of the crosslinked rubber can be stabilized or improved.
[0217] The heating conditions during secondary crosslinking are preferably 30 minutes to 48 hours at 80 to 350 °C.
[0218] As a crosslinking method other than heating to crosslink the fluorinated copolymer (A), a method of irradiating the fluorinated copolymer composition with radiation to crosslink the fluorinated copolymer (A) can be cited. Specific examples of the irradiated radiation include electron beams and ultraviolet light.
[0219] <Physical properties>
[0220] The compression set of the cross-linked rubber article under high temperature and high compression is preferably 70% or less, and more preferably 50% or less, from the perspective of good cross-linking of the fluorinated copolymer (A) and better shape recovery of the cross-linked rubber article after pressure.
[0221] The compression set of cross-linked rubber articles under high temperature and high compression was determined by the method described in the Examples section below.
[0222] <Applications>
[0223] Cross-linked rubber products are suitable for materials such as O-rings, sheets, gaskets, oil seals, diaphragms, and V-rings. In addition, it is also suitable for applications in heat-resistant and chemical-resistant sealing materials, heat-resistant and oil-resistant sealing materials, wire sheathing materials, sealing materials for semiconductor devices, sealing materials for liquid crystal display panel manufacturing devices, sealing materials for light-emitting diode manufacturing devices, corrosion-resistant rubber coatings, sealing materials for urea-based greases, rubber coatings, adhesive rubber, hoses, pipes, calendered sheets (rollers), sponges, rubber rollers, components for oil excavation, heat sinks, solution crosslinks, rubber sponges, bearing seals (urea-resistant greases, etc.), liners (chemical-resistant), automotive insulating sheets, insulating sheets for electronic devices, rubber belts for watches, endoscope seals (amine-resistant), corrugated hoses (processed from calendered sheets), water heater seals / valves, fender materials (marine and civil engineering, shipbuilding), fiber and non-woven fabrics (protective clothing, etc.), base sealing materials, rubber gloves, stators for single-shaft eccentric screw pumps, components for urea SCR systems, vibration damping agents, shock absorbers, sealants, additives to other materials, and toys.
[0224] Example
[0225] The present invention will now be illustrated by examples. Examples 1 to 3 are exemplary embodiments, and Examples 4 to 6 are comparative examples. However, the present invention is not limited to these examples.
[0226] [Determination of the composition of fluorinated copolymers]
[0227] The content (molar percentage) of each unit in the fluorinated copolymer (A-1) described later is determined by... 19 Calculated by F-nuclear magnetic resonance (NMR) analysis.
[0228] The content (mol%) of each unit in the fluorinated copolymers (B-1) and (B-2) described later was calculated by melt NMR analysis and fluorine content analysis. The content of the NAH unit was calculated by the following infrared absorption spectroscopy analysis.
[0229] [Infrared Absorption Spectroscopy Analysis]
[0230] The fluorinated copolymer (B-1), described later, was pressed into a film with a thickness of 200 µm. In the infrared absorption spectrum, the absorption peaks of the NAH-based units in the fluorinated copolymer (B-1) were all at 1778 cm⁻¹. -1 The absorbance of this absorption peak was measured using the molar absorptivity of NAH, which is 20810 mol / L. -1 ·l·cm -1 Determine the proportion of NAH units in the fluorinated copolymer (B-1).
[0231] [Glass transition temperature of fluorinated copolymers]
[0232] The glass transition temperature of each fluorinated copolymer was determined by the following method.
[0233] Take 10 mg of the test sample, and lower the sample temperature from room temperature (25℃) to -30℃ at a heating rate of 10℃ / min. Then, raise the temperature to 350℃ (1 st Plot the heat flux (mW) on the vertical axis and the temperature (°C) on the horizontal axis to obtain a curve. Based on the obtained curve, increase the temperature (1... st During heating, the minimum mW of T that indicates the baseline offset will be taken as the glass transition temperature of the fluorinated copolymer.
[0234] <Measurement Conditions>
[0235] Device: DSC 7020, manufactured by Hitachi High-Tech Science Co., Ltd.
[0236] Temperature program mode: lamp
[0237] Cooling unit: Electric cooling
[0238] Gas: Air 50 mL / min, Pressure: 0.1 MPa
[0239] Container: Aluminum
[0240] Sample weight: 10mg
[0241] Reference: Empty container
[0242] [Melting point of fluorinated copolymers]
[0243] At the glass transition temperature of the fluorinated copolymer, the temperature is raised to 350°C and then cooled at a heating rate of 10°C / min. The temperature at which the minimum heat flux (mW) at which the endothermic peak is observed is taken as the melting point (°C).
[0244] [MFR of fluorinated copolymers]
[0245] For each fluorinated copolymer, the mass (g) of the fluorinated copolymer flowing from a nozzle with a diameter of 2 mm and a length of 8 cm for 10 minutes (unit time) was measured using a melt indexer manufactured by TECHNOL SEVEN at 372 °C and a load of 49 N.
[0246] Compression permanent deformation under high temperature and high compression
[0247] Compression set was determined according to the methods described in ASTM D395 or JIS K6262. The O-rings (original thickness (wire diameter) = 3.5 mm) fabricated in each example were compressed to a compression rate of 25% using a compression device.
[0248] Next, the compression device with the compressed O-ring fixed in place was placed in an electric furnace at 300°C for 70 hours. Afterward, the compression device was removed from the furnace, and the O-ring was immediately removed. The removed O-ring was then placed in a constant temperature chamber at 23°C for 30 minutes, and the thickness of the O-ring (thickness after compression treatment) was measured. Two O-rings were used in the test, and the value was obtained by arithmetically averaging the measurements of the two O-rings. The compression set was calculated using the following formula. It should be noted that a compression set closer to 0% is better.
[0249] Compression set (%) = (Original thickness (straight diameter) - Thickness after 30 minutes of removing the O-ring from the compression unit (thickness after compression treatment) ÷ (Original thickness of the O-ring - Thickness of the spacer) × 100
[0250] Cracks under high temperature and high compression
[0251] For the O-rings subjected to compression permanent deformation under the above-mentioned high temperature and high compression conditions, the state of crack formation was visually confirmed.
[0252] [Plasma Resistance]
[0253] The O-rings fabricated in each example were cut in three places along the thickness direction, dividing the outer circumference into three equal parts, to prepare samples for measurement. Plasma etching was performed using a CPE-200AHM (manufactured by Kuei Semiconductor Corporation) under the following conditions: gas type: N2 / NF3 (NF3 mixing ratio: 20%), power: 300W, pressure: 26Pa, and irradiation time: 3 hours. The weight of the samples before and after treatment was measured, and the weight loss rate (mass %) was calculated. The weight was measured to 0.1 mg units using an Azpro electronic balance (device name: BCA64I-1SJP Sartorius).
[0254] [Manufacturing of Fluorinated Copolymer (A-1)]
[0255] After degassing a 20L stainless steel pressure reactor equipped with an anchor-type agitator, 7.2L of ultrapure water, 880g of a 30% (w / w) solution of C2F5OCF2CF2OCF2COONH4 (as emulsifier), 7.3g of 8CNVE, and 15.9g of a 5% (w / w) aqueous solution of disodium hydrogen phosphate dodecahydrate were added to purge the gas phase with nitrogen. While stirring with the anchor-type agitator at 375 rpm, 137g of TFE and 635g of PMVE were added into the container, and the internal temperature was raised to 80°C. The reactor internal pressure was 0.90 MPa (gauge pressure). 28mL of a 3% (w / w) aqueous solution of ammonium persulfate (APS) was added to initiate polymerization. The molar ratio of the monomers added before polymerization (hereinafter referred to as "initial added monomers") was TFE:PMVE:8CNVE = 26.3:73.3:0.4.
[0256] After polymerization begins, monomers are added as polymerization proceeds. Hereinafter, monomers added after polymerization begins will be referred to as "post-added monomers," and the monomers added after polymerization begins will be referred to as "post-added monomers."
[0257] TFE was injected when the reactor pressure dropped to 0.89 MPa, raising the reactor pressure to 0.90 MPa. This operation was repeated, with 3.7 g of 8CNVE, 74 g of PMVE, and 3.7 g of 8CNVE injected sequentially each time 119.3 g of TFE was injected.
[0258] When the polymerization rate decreases, add an appropriate amount of 3% (w / w) aqueous solution of APS. The total amount of 3% (w / w) aqueous solution of APS added after the start of polymerization is 35 mL.
[0259] At the end of the cycle with a total added mass of 1073.7g TFE, 119.3g of TFE was added. When the total added mass of the subsequently added TFE reached 1193g, the addition of the subsequent monomers was stopped, and the reactor temperature was cooled to 10°C to stop the polymerization reaction, yielding a latex containing a fluorinated copolymer. The polymerization time was 375 minutes. Furthermore, regarding the total added masses of each subsequent monomer—TFE 1193g, PMVE 666g, and 8CNVE 66.6g—the molar ratio is TFE:PMVE:8CNVE = 74.0:25.0:1.0.
[0260] Latex was added to a 5% (w / w) aqueous solution of potassium aluminum sulfate to cause the fluorinated copolymer to aggregate and separate. The fluorinated copolymer was filtered, washed with ultrapure water, and vacuum dried at 50°C to obtain a white fluorinated copolymer (A-1). The molar ratio of each unit in the obtained fluorinated copolymer (A-1) was TFE unit: PMVE unit: 8CNVE unit = 70.9: 28.6: 0.5.
[0261] In addition, the glass transition temperature of the fluorinated copolymer (A-1) is -3℃.
[0262] [Fluoropolymer (B-1)]
[0263] The product obtained by pulverizing the "fluorinated copolymer (X1-1)" in the Example section of International Publication No. 2016 / 017801 using a jet mill is designated as fluorinated copolymer (B-1). The molar ratio of the units in fluorinated copolymer (B-1) is NAH unit: TFE unit: PPVE unit = 0.1: 97.9: 2.0. The particle size D50 of fluorinated copolymer (B-1) is 2~3µm.
[0264] In addition, the glass transition temperature of the fluorinated copolymer (B-1) is 80°C, the melting point is 310°C, and the MFR is 17.6 g / 10 min (measurement temperature: 372°C).
[0265] [Fluoropolymer (B-2)]
[0266] As the fluorinated copolymer (B-2), MJ-310 (manufactured by Chemours-Mitsui Fluoroproducts Co., Ltd.) was used. The molar ratio of each unit in the fluorinated copolymer (B-2) was TFE unit:PPVE unit = 98.7:1.3.
[0267] In addition, the glass transition temperature of the fluorinated copolymer (B-2) is 90°C, the melting point is 310°C, and the MFR is 15 g / 10 min (measurement temperature: 372°C).
[0268] [Example 1]
[0269] For fluorinated copolymer (A-1) (100 parts by weight) and fluorinated copolymer (B-1) (20 parts by weight), a roll mixer (φ8 inch × 18 inch test roll mixer, manufactured by Yageshi Corporation) was used. The speed of the F roll (the operator-side roll of the two rolls in the roll mixer) was set to 9 rpm, and the speed of the R roll (the opposite side of the operator's side of the two rolls in the roll mixer) was set to 13 rpm. The mixture was mixed at 23°C for 10 minutes to obtain a sheet-like mixture 1 with a thickness of 1.5 mm (premixing process). Immediately after the premixing process, the surface temperature of the obtained mixture 1 was measured using a radiation thermometer (IT-545S, manufactured by Horiba Manufacturing Co., Ltd.). The result showed that 50°C was below the glass transition temperature of the fluorinated copolymer (B). Next, the obtained mixture 1 was cut into dimensions of 80 mm in length × 10 mm in width × 1.5 mm in thickness, with the length direction parallel to the roll rotation direction.
[0270] Next, using a LABO PLASTOMILL (model 4C150, manufactured by Toyo Seiki Co., Ltd.) and a mixer 30, the mixing temperature was set to 250°C, and the cut mixture 1 was fed into the mixer (feed amount 50g). Then, the mixing was carried out at a speed of 100 rpm and a processing time of 2 minutes to obtain composition 1 (mixing process).
[0271] BOAP (2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 1 part by mass) was added to composition 1, and the mixture was kneaded at 23°C for 10 minutes using the above-mentioned roller mixer to obtain fluorinated copolymer composition 1 (sub-kneading process).
[0272] The obtained fluorinated copolymer composition 1 was hot-pressed at 180°C for 10 minutes using a hydraulic press (model: SA-301 50T, manufactured by TESTER Industries, with a press head diameter of 180 mm) to obtain an O-ring (size: P-26) (1st crosslinking). Next, the obtained O-ring was heated at 90°C for 2 hours in a nitrogen atmosphere using an oven (DN411I, manufactured by Yamato Scientific), then the temperature was increased to 200°C for 2 hours, heated at 200°C for 4 hours, and then increased to 305°C for 2 hours, and heated at 305°C for 12 hours, thus performing a second crosslinking. The O-ring was then cooled to 23°C to obtain the O-ring of Example 1.
[0273] [Example 2~Example 5]
[0274] The O-rings in Examples 2 to 5 were obtained using compositions 2 to 5 and fluorinated copolymer compositions 2 to 5, except that the fluorinated copolymers and mixing conditions shown in the table were changed. The same steps as in Example 1 were followed.
[0275] It should be noted that in the manufacturing process of compositions 2 to 5, the surface temperature of each mixture immediately after the premixing process was measured using a radiation thermometer (IT-545S, manufactured by Horiba Manufacturing Co., Ltd.), and the result showed that 50°C was below the glass transition temperature of the fluorinated copolymer (B).
[0276] [Example 6]
[0277] Fluorinated copolymer (A-1) (100 parts by mass) and fluorinated copolymer (B-1) (20 parts by mass) were mixed in a roller mixer at 23°C for 10 minutes to obtain mixture 6. Immediately after mixing, the surface temperature of composition 6 was measured using a radiation thermometer (IT-545S, manufactured by Horiba Corporation), and the result was 50°C.
[0278] Next, without performing a mixing process, BOAP (2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 1 part by mass) was added to mixture 6, and the post-mixing process was performed in the same manner as in Example 1 to obtain the O-ring of Example 6.
[0279] In Table 1, the "-" in "compression permanent deformation under high temperature and high compression" in Examples 4 to 6 indicates that the O-ring developed cracks after the above-mentioned high temperature and high compression compression permanent deformation test, so it could not be measured.
[0280] [Table 1]
[0281]
[0282] As shown in Table 1, it was confirmed that if the composition obtained by this manufacturing method is used, a cross-linked rubber article that can suppress cracking under high temperature and high compression and has excellent plasma resistance can be formed.
[0283] Based on the comparison of Examples 1 to 3, it was confirmed that when the content of fluorinated copolymer (B) in the mixture is less than 30 parts by mass relative to 100 parts by mass of fluorinated copolymer (A), the compression set under high temperature and high compression is better.
[0284] It should be noted that the entire contents of the specification, claims and abstract of Japanese Patent Application No. 2023-220825, filed on December 27, 2023, are incorporated herein as a disclosure of the specification of this invention.
Claims
1. A method for manufacturing a composition, comprising a mixing step of mixing a mixture comprising a fluorinated copolymer (A) and a fluorinated copolymer (B) above the glass transition temperature of the fluorinated copolymer (B), The fluorinated copolymer (A) has tetrafluoroethylene-based units and perfluoro(alkyl vinyl ether)-based units. The fluorinated copolymer (B) is a copolymer different from the fluorinated copolymer (A), having units based on monomers having at least one functional group selected from the group consisting of carboxyl groups and groups represented by formula (X), units based on tetrafluoroethylene, and units based on perfluorinated (alkyl vinyl ethers). Formula (X) *-CO-O-CO-* In equation (X), * represents the bonding position.
2. The method for manufacturing the composition according to claim 1, wherein, The fluorinated copolymer (A) comprises units having nitrile groups.
3. The method for manufacturing the composition according to claim 1 or 2, wherein, The mixing process is a process of mixing the mixture above the melting point of the fluorinated copolymer (B).
4. The method for manufacturing the composition according to claim 1 or 2, wherein, In the mixture, the content of the fluorinated copolymer (B) is less than 50 parts by mass relative to 100 parts by mass of the fluorinated copolymer (A).
5. A method for manufacturing the composition according to claim 1 or 2, wherein, The fluorinated copolymer (A) is a fully fluorinated fluorinated copolymer.
6. A crosslinked rubber article formed by crosslinking the fluorinated copolymer (A) in a composition manufactured by the method of manufacturing the composition according to claim 1 or 2 using a crosslinking agent.
7. The cross-linked rubber article according to claim 6, which is a sealing material for semiconductor devices.
Citation Information
Patent Citations
Supply apparatus of telephone, electricity, gas and service water for rotary house and waste water discharge apparatus
JP1983033657A
Fluorine-containing elastic copolymer, process for the production thereof, and crosslinked rubber articles
WO2010082633A1
Resin powder, method for producing same, complex, molded article, method for producing ceramic molded article, metal laminated plate, print substrate, and prepreg
WO2016017801A1
Fluorocopolymer composition and crosslinked rubber article
WO2021210502A1